2023
DOI: 10.3923/ajps.2023.206.214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Applying Seaweed Extracts and NPK Fertilizer on Vegetative Growth, Flowering Traits and Seed Yield of Borage (Borage officinalis L.)

Abstract: Background and Objective: Borage is a medicinal plant with different culinary and medicinal uses. It is also cultivated for commercial oil production. Little information is available regarding the influence of the type of fertilizer on borage performance under different environmental conditions. Therefore, there is a need to determine the impact of some fertilizers such as seaweed and NPK on several agronomic parameters. Materials and Methods: Fertilizer treatments include seaweed (2 g LG 1 ) and NPK (2 g LG 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The other treatment combinations at 80, 110, and 140 DAT showed differences, but the height of the seedlings was still below the value found at the highest dose, as indicated in Figure 1. NPK fertilizer application was discovered to influence growth of seedlings [14]. The high growth rate of oil palm plants observed in this study (Figure 1) was consistent with other results reported by [15] that the addition of NPK fertilizer (16:16:16) increased plant height.…”
Section: A Plant Heightsupporting
confidence: 91%
“…The other treatment combinations at 80, 110, and 140 DAT showed differences, but the height of the seedlings was still below the value found at the highest dose, as indicated in Figure 1. NPK fertilizer application was discovered to influence growth of seedlings [14]. The high growth rate of oil palm plants observed in this study (Figure 1) was consistent with other results reported by [15] that the addition of NPK fertilizer (16:16:16) increased plant height.…”
Section: A Plant Heightsupporting
confidence: 91%
“…Additionally, the NPK nutrients are essential for respiration, osmotic control, transpiration, photosynthesis and other processes [19]. Moreover, Applying basil plant with NPK fertilizer produced the highest active ingredients contents [20]. As was previously noted, both NPK fertilization and bio-fertilization treatments (each separately) boosted guaran output.…”
Section: Guaran Productionmentioning
confidence: 82%